Research in haemophilia B – approaching the request for high evidence levels in a rare disease. (11th December 2014) - Berger, K.; Schopohl, D.; Hilger, A.; Behr Gross, M. –E.; Giangrande, P.; Peyvandi, F.; Seitz, R.; Schramm, W.
Summary Payers in European countries request studies with high levels of evidence for decision making also for rare diseases like haemophilia B (HB). The objective of the study was to determine the status quo of current studies in HB regarding the overall level of evidence generated. The methods used for performing the study were systematic literature research in EMBASE and MEDLINE, search terms 'HB' and 'factor IX' (FIX). The inclusion criteria were journal articles (JA), conference abstracts (CA), English language, published between January 2009 and March 2013, studies only; screening of titles, abstracts, full texts subsequently. ClinicalTrials.gov search: unpublished registered trials (RT) concerning HB or FIX. The analysis was performed on research topic, sponsor, recruitment status and study design. Screening of 1639 hits yielded 31 JA describing 35 studies, and 62 CA. FIX was subject of 21 studies (60.0%) and 29 CA (46.8%). Seven studies focused on various aspects of HB, six on haemophilia studies with separate HB data. Screening of 173 hits from ClinicalTrials.gov yielded 42 RT. Overall, 32 RT (76.2%) related to FIX. Measurement of health‐related quality of life (HRQoL) was identified in none of these studies, four CA (6.5%), four RT (9.5%). Randomized study design was found in one study (2.9%), four RT (9.5%). Three studies (8.6%) and seven RT (16.7%) were prospective, observational and comparative. The majority of published clinical studies do not meet payers' expectations for evidence. Therefore, clinical investigation concepts addressing randomization, outcomes research including HRQoL and comparison of therapy options should be discussed. Refined statistical methods and exploitation of complementary real‐life data sources may fill current evidence gaps concerning rare diseases.